2005
DOI: 10.2203/dose-response.003.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Oxidative Stress Responses by Dioxin and other Ligands of the Aryl Hydrocarbon Receptor

Abstract: ᮀTCDD and other polyhalogenated aromatic hydrocarbon ligands of the aryl hydrocarbon receptor (AHR) have been classically considered as non-genotoxic compounds because they fail to be directly mutagenic in either bacteria or most in vitro assay systems. They do so in spite of having repeatedly been linked to oxidative stress and to mutagenic and carcinogenic outcomes. Oxidative stress, on the other hand, has been used as a marker for the toxicity of dioxin and its congeners. We have focused this review on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 170 publications
4
52
1
1
Order By: Relevance
“…Inactivation of aconitase activity, which is a measure of oxidative stress, occurred in response to TCDD in C57BL/6 mice, but not in resistant DBA/2 mice [4,12]. The studies also showed that iron administration potentiated TCDDinduced toxicity, including hepatic porphyria in C57BL/6 mice, via an oxidative process, but did not do so in the DBA/2 mice.…”
Section: Role Of the Ahr In Production Of Oxidative Stressmentioning
confidence: 91%
See 3 more Smart Citations
“…Inactivation of aconitase activity, which is a measure of oxidative stress, occurred in response to TCDD in C57BL/6 mice, but not in resistant DBA/2 mice [4,12]. The studies also showed that iron administration potentiated TCDDinduced toxicity, including hepatic porphyria in C57BL/6 mice, via an oxidative process, but did not do so in the DBA/2 mice.…”
Section: Role Of the Ahr In Production Of Oxidative Stressmentioning
confidence: 91%
“…Similarly, initial studies concerning the role of ROS and oxidative stress focused primarily on the liver [1, 2, 5, 13-18, 33, 38-41, 52, 97]. These studies clearly demonstrated the roles of lipid peroxidation, DNA damage, production of ROS, altered membrane fluidity, and modulation of glutathione and glutathione metabolizing enzymes in the hepatotoxicty of TCDD and related chemicals [2][3][4]97].…”
Section: Oxidative Stress and Hepatotoxicitymentioning
confidence: 98%
See 2 more Smart Citations
“…Several lines of evidence indicate that activation of the AhR might lead to oxidative stress following exposure to DLCs (Reichard et al, 2005;Stohs, 1990). It has been shown that ROS, such as superoxide and hydrogen peroxide, can be generated by the incomplete reduction of O 2 by cytochrome P450 enzymes that are regulated by the AhR (Shertzer et al, 1998).…”
Section: Oxidative Stressmentioning
confidence: 99%